Why are married men working so much? The macroeconomics of bargaining between spouses - John Knowles (Institute for the Study of Labor (IZA), 2007)
The rise in per-capita labor over the last 30 years is difficult to explain in a standard macroeconomic model because rising wages of women should have lead to a large rise in husband's leisure. This paper argues that home production and bargaining are both essential for understanding these trends, and develops an equilibrium model of marriage and bargaining. Calibration to US data suggests that the bargaining position of husbands has deteriorated with the closing of the gender gap in wages, that the decline of home-equipment prices plays a role in the rise in per-capita hours, and that the labor trends are consistent with stationarity along a balanced-growth path.
Keywords: 330; Familienökonomik; Verhandlungsmacht; Geschlecht; Arbeitsangebot; Männer; Arbeitszeit; Frauenerwerbstätigkeit; USA